Dip pen nanolithography and its potential for nanoelectronics - Rosner, Bjoern (2012)
Dip pen nanolithography (DPN) is a patterning technique for nanoscale science and engineering based on scanning probe microscopy. Its main advantages are very high resolution, the unique capability to deposit many different materials directly onto a substrate and low cost of ownership. We present here new research and development efforts that demonstrate the potential of DPN as a tool to produce nanoelectronic devices and circuits. We show the direct deposition of electronic materials as well as the use of external accessories to accelerate the development phase of nanoelectronic components.